Performance of homogeneous charge compression ignition engine fuelled with used cooking oil-based biodiesel - Mossa, Muntasser Abdulabbas (2019)
Energy is increasingly used around the globe daily for transportation purposes whether in air, land, or sea. The majority of energy used in the transportation sector is extracted from the combustion process in engines. The amount of energy extracted during the combustion process to create necessary power produces undesired amounts of emission levels as by-products. Many countries have strengthened their energy policies and proposed more stringent emission standards to tackle this issue. To decrease engine emissions, many researchers are investigating the effects of using biodiesel in conventional spark ignition (SI) or compression ignition (CI) engines and its effect on engine performance. Some have developed biodiesel fuels to suit these engines, while others have modified the engines instead giving rise to the Homogeneous Charge Compression Ignition (HCCI) engine. In this study, a CI engine was modified to operate in HCCI mode and used cooking oil (UCO)-based biodiesel was used as fuel. The UCO was obtained from the market and was transesterified in the Institute of Biotechnology, Universiti Putra Malaysia`. The purpose of this study is to investigate the performance of a HCCI engine fuelled with biodiesel and its effect on emissions levels and engine power. It is expected that the HCCI engine will have improved emission levels compared to the conventional CI engine. Furthermore, using biodiesel as a fuel can further improve emission levels. In this study, the engine used was a single-cylinder, 4-stroke diesel engine, air-cooled, and with a rated speed of 3600 rpm and displacement of 0.219 liters. The engine was then converted to operate in HCCI mode using a pre-heating method. The engine was run at different speeds of 1600 rpm, 1800 rpm, 2000 rpm, and 3600 rpm in direct injection (DI) mode, followed by the HCCI mode, run at one engine speed of 2700 rpm, with different biodiesel blend rates and intake temperature. The engine was fuelled with UCO biodiesel blends of B5, B10, B15, and B20, where B5 indicates a blend of 5% UCO and 95% diesel. The results showed that when the engine was run in diesel mode with UCO as fuel, the engine torque and brake power reduced and fuel consumption increased. The emission level of NOx, CO, and UHC was also reduced but CO2 emission increased. When the engine operates in HCCI mode using UCO biodiesel with different blend ratio, improved emission level was observed, where the CO emission levels decrease with increased blend ratio that because more oxygen with lower carbon is present in biodiesel blends compared to diesel fuel, which has better combustion. The amount of oxygen in UCO biodiesel helped create better combustion, leading to a reduced CO emission level. In DI mode, the engine yielded high NOx of 142 ppm with diesel fuel, however, this value decreases to 10 ppm when the engine was run in HCCI mode at temperature of 70ºC. The NOx emission was further decreased to 5 ppm with increased intake air temperature to 90ºC, that because the intake temperature was controlled in HCCI mode. The NOx emission level decreased when run in HCCI engine and when increased the intake temperature that due to improvement in the combustion. It can be concluded from the findings that when the engine operated in HCCI mode fuelled with UCO-based biodiesel, the emissions levels were improved without sacrificing the engine performance significantly, which the main aim of this thesis.